Transcultural adaptation of the Johns Hopkins Fall Risk Assessment Tool - Maria Carmen Martinez; Viviane Ernesto Iwamoto; Maria do Rosário Dias de Oliveira Latorre; Adriana Moreira Noronha; Ana Paula de Sousa Oliveira; Carlos Eduardo Alves Cardoso; Ifigenia Augusta Braga Marques; Patrícia Vendramim; Paula Cristina Lopes; Thais Helena Saes de Sant'Ana
ABSTRACT Objective: to perform the transcultural adaptation and content validity analysis of the Johns Hopkins Fall Risk Assessment Tool to assess both fall risk and fall-related injury risk for hospitalized elderly in Brazil. Method: the transcultural adaptation consisted of translating the scale to Portuguese (Brazil), back-translating it into its language of origin, establishing a consensus version, and having an expert committee verify its transcultural equivalence. Content assessment was conducted by a committee of judges, ending with the calculation of the items and scales' content validity index. Nurses tested the tool. Results: the scale's translated version went through two evaluation rounds by the judges, based on which, the items with unsatisfactory performance were changed. The content validity index for the items was ≥80.0% and the global index 97.1%. The experimental application showed the scale is user-friendly. Conclusion: the scale presents valid content for the assessment of fall risk and risk of fall-related injuries and is easy to use, with the potential to contribute to the proper identification of risks and the establishment of care actions.